Analisis Nilai Moral dalam Novel Suluh Rindu Karya Habiburrahman El Shirazy: Kajian Sosiologi Sastra - Mala Olivia; Hany Uswatun Nisa; Elinda Umisara (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The purpose of this study is to analyze the foundation of the novel Suluh Rindu by Habiburrahman El Shirazy, analyze the moral values ​​in the novel Suluh Rindu by Habiburrahman El Shirazy, and study the sociology of literature of the novel Suluh Rindu by Habiburrahman El Shirazy. This study is a qualitative descriptive study. The data in this study are in the form of researcher notes in the form of words, phrases or sentences. The data source in this study is a document in the form of a literary novel entitled Suluh Rindu by Habiburrahman El Shirazy. The data collection technique used in this study is the reading and note-taking technique. The reading technique is carried out by reading the entire novel Suluh Rindu by Habiburrahman El Shirazy. While the recording is done by recording data in the form of words, sentences, and paragraphs that show the content of moral values ​​and religiosity in the novel Suluh Rindu by Habiburrahman El Shirazy. Increasing the degree of trustworthiness in research using triangulation of analysis results. The data analysis technique in this study uses the hermeneutic reading technique, namely reading, noting and drawing conclusions. The results of the study in the form of moral values ​​contained in the novel Suluh Rindu by Habiburrahman El Shirazy are classified into three forms, namely: Human relations with God, Human relations with themselves, and Human relations with other humans.